2006
DOI: 10.1007/s10658-006-9003-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of potato virus Y isolates from tomato crops in northeast Spain

Abstract: A collection of 39 potato virus Y (PVY) isolates from tomato, originating from several commercial crops grown in north-east Spain, was characterised by biological, serological and molecular assays. In general, no correspondence among the three different assays was observed. The results of biological characterization by inoculation of PVY isolates to Nicotiana spp. and pepper plants did not coincide with the differentiation provided by enzyme-linked immunosorbent assay (ELISA) using monoclonal antibodies specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Thus, samples 80.11 and 80.12 tested positive for PMoV, which could not be analysed by ELISA since no antiserum was available, whereas samples 209.5, 210.3, 211.2 and 211.3 rendered positive for PVY. Much genetic and serological diversity of PVY isolates infecting tomato in Spain has been reported (Aramburu et al 2006). The results of this work showed that some PVY isolates from tomato only provided a weak positive reaction when the ELISA test was achieved using polyclonal antiserum, and some of them were not detected when specific monoclonal antibodies were used.…”
mentioning
confidence: 74%
“…Thus, samples 80.11 and 80.12 tested positive for PMoV, which could not be analysed by ELISA since no antiserum was available, whereas samples 209.5, 210.3, 211.2 and 211.3 rendered positive for PVY. Much genetic and serological diversity of PVY isolates infecting tomato in Spain has been reported (Aramburu et al 2006). The results of this work showed that some PVY isolates from tomato only provided a weak positive reaction when the ELISA test was achieved using polyclonal antiserum, and some of them were not detected when specific monoclonal antibodies were used.…”
mentioning
confidence: 74%
“…Potato virus Y (PVY), a member of the Potyvirus genus (Potyviridae family), is the most economically important virus of potato crops, affecting tuber yield and quality and resulting in losses of 10–90% depending on the year, cultivar and location (De Bokx and der van Want, ; Valkonen, ). PVY can also infect other Solanaceae species such as bell pepper, tomato and tobacco (Aramburu et al ., ). PVY is mechanically transmitted by more than 40 aphid species in a non‐persistent manner (Brunt, ).…”
Section: Introductionmentioning
confidence: 97%
“…Biological classification of PVY strains is based mostly on the host from which they were isolated 26 . Strong strain-host specificity has been observed in potato and pepper 27 whereas tomato seems poorly selective with respect to symptoms induced by different PVY isolates [27][28][29][30][31][32] . Tomato plants infected by PVY O or PVY C strains show crinkling of young leaves often followed by necrotic mottling and necrosis of the veins on the lower leaf surface while fruits remain usually symptomless 33 .…”
mentioning
confidence: 99%